P-85 How a hospice admiral nurse community of practice can impact on practice. Issue Volume 8: Issue (2018)Supplement 2 (November 2018) - Scates, Caroline; Dening, Karen Harrison
Abstract : People with dementia often do not receive the same access to end of life care as people dying from other illnesses (Hospice UK, 2015). Despite dementia being acknowledged as a life limiting illness (van der Steen, Radbruch, Hertogh et al ., 2014) people living with this illness often do not have the same access to palliative care services as people with other life-limiting conditions, despite similar levels of complexity. Dementia UK have experienced a growing level of interest in commissioning the model of Admiral Nursing from hospices. In 2016 an Admiral Nursing Hospice Community of Practice started exploring how Admiral Nurses can support each other, and their colleagues to ensure consistency of practice and ensure people with dementia receive good end-of-life care. Communities of Practice have been defined as 'groups of people who share concern or passion for something they do and learn how to do it better' (Wenger & Wenger-Trayner, 2015). This Community of Practice aimed to provide peer support to hospice-based Admiral Nurses and develop a model of practice, alongside disseminating skills and knowledge to Admiral Nurses in other settings. The Admiral Nursing Hospice Community of Practice was first convened in December 2016 and has since met regularly to develop the model of practice. There are now nine Admiral Nurses working in an end of life/hospice setting across the country with a further six posts at recruitment stage with more in the pipe-line. The Community of Practice will continue to explore how to increase resources available for Admiral Nurses on end of life care and act as an expert reference group for Dementia UK. Currently the group are sharing practice from their settings; for example, assessment documentation, referral criteria and leaflets for family carers. Hospice-based Admiral Nurses are an innovative way of ensuring people with dementia receive more equality from hospices, and the hospice-based Admiral Nurses will be supported by this growing Community of Practice.